Prevalence and clinical characteristics associated with peripheral neuropathy amongst persons on HAART in Busia County, Kenya - John N. Mukoma; Joseph M. Matheri; Nassib Tawa (AOSIS, 2020)
Background: Despite improved immunological and viral load control, the prevalence of HIV/AIDS-related peripheral neuropathy among survivors on highly active antiretroviral therapy (HAART) is rising globally raising public health concerns. Objectives: To determine the prevalence and clinical characteristics of peripheral neuropathy amongst persons on HAART attending Comprehensive Care Clinics in Busia County, Kenya. Method: This cross-sectional descriptive quantitative study utilised purposive sampling and included 289 adults living with HIV/AIDS. Data collection was undertaken using the Clinical HIV Associated Neuropathy Tool (CHANT) and analysed using the Statistical Package for the Social Sciences version 25.0. Results: Of people on HAART, 68.17% (197 amongst 289) had peripheral neuropathy. The majority were female 76.8% (n = 222), 38.1% (n = 110) were between 41 and 50, and 35% (n = 101) were widowed. The most common primary symptom was reduced right foot big toe vibration (76.8%, n = 222). There was a strong positive relationship (r = 0.621, P = 0.000) between foot vibration and illness. There was a statistically significant influence of demographic characteristics of persons on HAART on PN as they accounted for 98.5% of the variance (R2 = 0.985). Conclusion: Peripheral neuropathy is prevalent and is significantly influenced by socio-demographic characteristics of persons on HAART-PN. Early diagnosis and exercise guidance by physiotherapists is key in forestalling severe symptoms, disability and poor quality of life. Clinical implications: There is need to screen persons living with HIV on HAART for PN to establish their medical, physiotherapy and rehabilitation needs. Early diagnosis will encourage healthcare workers to start interventions to prevent progression of impairment, onset of disability and decrease in quality of life. Therefore, adaptation of PN screening tools and physiotherapeutic interventions should be considered.